2016
DOI: 10.1007/s00105-016-3913-0
|View full text |Cite
|
Sign up to set email alerts
|

Partielles Ansprechen einer Lichturtikaria auf Omalizumab

Abstract: The treatment of solar urticaria is regarded as difficult. In some cases good responses to the anti-IgE antibody omalizumab (Xolair®), approved for treatment of chronic spontaneous urticaria, have been reported. We report on a 50-year-old Caucasian woman who for the last 5 years has developed localized itching and stinging erythemas following exposure to sunlight accompanied sometimes by anaphylactic reactions. Oral antihistamines in three- to four-fold doses and a topical sun screen had been only partially ef… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 8 publications
0
3
0
Order By: Relevance
“…87,89 Of all CIndU subtypes, solar urticaria had the highest number of publications on omalizumab use. Of 18 publications that included 36 cases, the majority showed that omalizumab successfully controlled symptoms, whereas 4 included patients with a partial response, 39,42,57,58 and 3 showed failure to respond to treatment. 40,59,60 The strongest evidence came from a multicenter, prospective, phase II study including 10 antihistamine-refractory patients with solar urticaria that greatly affected their QoL (DLQI score of >10).…”
Section: Physical Urticariasmentioning
confidence: 99%
“…87,89 Of all CIndU subtypes, solar urticaria had the highest number of publications on omalizumab use. Of 18 publications that included 36 cases, the majority showed that omalizumab successfully controlled symptoms, whereas 4 included patients with a partial response, 39,42,57,58 and 3 showed failure to respond to treatment. 40,59,60 The strongest evidence came from a multicenter, prospective, phase II study including 10 antihistamine-refractory patients with solar urticaria that greatly affected their QoL (DLQI score of >10).…”
Section: Physical Urticariasmentioning
confidence: 99%
“…Unfortunately, traditional therapies are often unable to provide adequate and safe responses in solar urticaria, leading to a reduce quality of life in individuals affected, who are forced to significantly limit their normal activities [19, 20, 21].…”
Section: Discussionmentioning
confidence: 99%
“…Despite the effectiveness shown by omalizumab in many cases of solar urticaria refractory to conventional therapies, a certain proportion of subjects remain who do not respond satisfactorily [18, 19, 20, 21], and it is therefore necessary to study more thoroughly the pathogenetic mechanism of the disease in order to be able to select the patients and establish with confidence the most appropriate treatment.…”
Section: Discussionmentioning
confidence: 99%